Slow dance : a novel [compact disc, unabridged] - Rowell, Rainbow (HarperAudio, 2024)
Shiloh fled Omaha as soon as she could. So when a high school friend invites Shiloh to his wedding, the last thing she wants is to catch up with the old gang. But she buys a new dress, puts on some makeup, and pins a silk flower over her heart, hoping, and also worrying, that she might see Cary, the boy she never realized she loved until he was lost.